Acquisition of alcohol use of in a group of mexican adolescents: the effect of the relationship with friends - Facundo, Francisco Rafael Guzmán; Castillo, Maria Magdalena Alonso (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2005)
This study involved a group of 98 Mexican adolescents and aimed to get to know the stages of acquisition of alcohol use among adolescents who belong to youth gangs and the effect of the risk factor: relations with friends who show problematic behavior in the consumption of alcoholic drinks. The results showed that these adolescents were in the maintenance stage. On the other hand, we found a significant effect (F = 4.37, p = .015) of the relationship with friends who display problematic alcohol consumption behavior.